Electrochemical corrosive agent, quantitative statistical method for carbides in martensitic stainless steel and application
The electrochemical method provides a precise determination of hardness and wear resistance by providing a precise determination of carbide content in martensitic stainless steel using the electrochemical method provides a precise determination of carbide content in martensitic stainless steel using the electrochemical method provides a precise determination of carbide content in martensitic stainless steel.
Patent Information
- Application Number
- CN202411279301.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-13
AI Technical Summary
Existing methods for analyzing the morphology and distribution of carbides in martensitic stainless steel are inadequate, as they fail to provide clear visualization and quantification, often using toxic substances and cumbersome processes that complicate the observation of grain boundaries and carbide distribution.
An electrochemical etchant comprising a pretreatment solution, electrochemical solution, and post-treatment solution, which includes potassium thiocyanate, sulfuric acid, and water, is used to corrode the stainless steel under controlled voltage and current, followed by data reconstruction and processing to obtain quantitative carbide content.
The method provides clear visualization and quantification of carbide morphology and distribution, enhancing the observation of carbides and steel matrix contrast, allowing for precise determination of hardness and wear resistance.
Smart Images

Figure CN119125208A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbide detection in martensitic stainless steel, and in particular relates to an electrochemical corrosive agent, a quantitative statistical method for carbides in martensitic stainless steel and an application thereof. Background Art
[0002] High carbon martensitic stainless steel, due to its high carbon and chromium content, greatly improves hardness and wear resistance while ensuring corrosion resistance, and is widely used in the manufacture of high-quality knives, scissors, surgical knives, etc. Increasing the carbon content, a martensitic structure with a high dislocation density is obtained after quenching, and then tempering is performed to eliminate the internal stress generated during quenching to obtain a uniform and stable structure. After tempering, carbides attached to the ferrite will precipitate, and the carbides are usually distributed in a dispersed form, which will improve the hardness and wear resistance of martensitic stainless steel. However, the precipitation of chromium carbides in stainless steel will increase with the increase of C content in the steel. Therefore, with the increase of grain boundary carbides, serious Cr deficiency will occur near the grain boundaries, which will increase the potential difference near the grain boundaries and inside the grain boundaries, thereby reducing the corrosion resistance of the steel.
[0003] The metallographic structure of this type of stainless steel after quenching is generally martensite matrix + eutectic carbide + residual austenite + secondary carbide. The shape, size and distribution of carbides in martensitic stainless steel have a great influence on the material properties. Therefore, it is necessary to analyze the morphology and proportion of carbides in martensitic stainless steel.
[0004] At present, the metallographic structure of stainless steel is observed after being corroded by ferric chloride, hydrochloric acid and alcohol corrosive agents, but the corrosion time of ferric chloride, hydrochloric acid and alcohol is difficult to control, it is difficult to clearly show the grain boundaries of the original austenite grains, and it is difficult to rate the grain size. As for the morphology of high-carbon martensitic stainless steel, it is observed after being corroded by corrosive agents. One of the existing corrosive agents is composed of picric acid, concentrated hydrochloric acid, alcohol and detergent, and picric acid is a toxic substance. The second existing corrosive agent is potassium permanganate corrosive agent, including potassium permanganate and sulfuric acid aqueous solution; however, after the stainless steel is corroded by the potassium permanganate corrosive agent, the morphology and distribution of carbides in the martensitic stainless steel and the positional relationship with the matrix cannot be fully displayed, the three-dimensional sense is not strong, and the contrast difference is not obvious.
[0005] As for the quantitative analysis of carbides in high carbon martensitic stainless steel, acid dissolution analysis or electrolysis is generally used. The acid dissolution method may produce harmful gases during the acid dissolution process. The electrolysis method is to separate and identify carbides in low alloy steel and then conduct quantitative analysis. However, the operation process of the electrolysis method is complicated and the process is cumbersome, which is not easy to promote. Summary of the invention
[0006] To solve the above problems, the present invention proposes a quantitative statistical method for the morphology and proportion of carbides in electrochemical corrosive agents and martensitic stainless steel. The method combines corrosive agents and electrochemical methods to corrode martensitic stainless steel. After corrosion, the morphology and distribution of carbides in the stainless steel sample are easy to observe and distinguish, and the contrast difference between carbides and steel matrix is obvious. The method can quantitatively calculate the carbide content in high-carbon martensitic stainless steel. The result is more intuitive and vivid.
[0007] The present invention is achieved through the following technical solutions:
[0008] One of the purposes of the present invention is to provide an electrochemical etchant, comprising a pretreatment solution, an electrochemical solution and a post-treatment solution;
[0009] The electrochemical solution comprises potassium thiocyanate, sulfuric acid and water; the weight volume ratio of the potassium thiocyanate, sulfuric acid and water is (1g-5g): (20ml-70ml): (300ml-500ml).
[0010] The electrochemical corrosive agent provided by the present invention corrodes the steel substrate under the action of voltage or current applied in stages and gradient cycles, so that the morphology and distribution of carbides on the surface of the stainless steel are easy to observe and distinguish, and the contrast difference between the carbides and the steel substrate is obvious.
[0011] In some possible implementations, the pretreatment solution includes 30 to 50 parts by volume of nitric acid and 10 to 20 parts by volume of anhydrous ethanol. In this case, the purpose of pretreating the stainless steel surface is to prevent the corrosion of the metal material. The metal surface is very clean and very active, and is easily corroded, so it must be passivated immediately to form a protective film on the cleaned metal surface to slow down the corrosion.
[0012] In some other possible implementations, the pretreatment solution includes concentrated nitric acid with a concentration of 8 mol / L or more or a mass fraction of 40% or more. In this case, the steel surface is passivated.
[0013] In some other possible implementations, the electrochemical solution includes a hydrochloric acid aqueous solution with a mass concentration of 10% to 24%. In this case, the hydrochloric acid aqueous solution can also corrode the stainless steel substrate under the action of voltage or current to expose carbides.
[0014] In some possible implementations, the post-treatment liquid includes at least one of anhydrous ethanol, acetone, and isopropanol. In this case, the post-treatment liquid not only removes the residue of the electrochemical corrosion solution, but also protects the sample surface to prevent corrosion and carbide from falling off.
[0015] In some possible implementations, the volume fraction of the post-treatment liquid is 2 to 10 parts.
[0016] The second object of the present invention is to provide a quantitative statistical method for carbides in martensitic stainless steel using the electrochemical corrosive agent of the present invention, comprising the following steps:
[0017] The clean stainless steel sample is pre-corroded by using a pre-treatment liquid to obtain a pre-treated sample;
[0018] Performing electrochemical corrosion treatment on the pretreated sample using an electrochemical solution to obtain an electrochemically corroded sample;
[0019] Post-treating the electrochemical corrosion sample with a post-treatment liquid to obtain a sample to be tested;
[0020] The energy spectrum data of the sample to be tested is obtained, and data reconstruction and data processing are performed to obtain quantitative data of the carbide content in the sample to be tested.
[0021] The quantitative statistical method provided by the present invention can quantitatively analyze the carbide content of the stainless steel sample, thereby providing a reference for judging the hardness and wear resistance of the martensitic stainless steel.
[0022] In some possible implementations, obtaining the clean stainless steel sample comprises the steps of:
[0023] After sampling the stainless steel, the cut surface is polished and ultrasonically cleaned with anhydrous ethanol to obtain the clean stainless steel sample.
[0024] In the above-mentioned process of obtaining the clean stainless steel sample, grinding the cut surface can remove the grinding cutting marks and make the cut surface smooth; using anhydrous ethanol for ultrasonic cleaning to remove the oil film on the surface of the stainless steel sample. The temperature, power and time of the ultrasound can be adjusted according to the actual situation of removing the oil film, and there is no special requirement. The size of the clean stainless steel sample can be cut and obtained according to actual needs. As an example, the size of the clean stainless steel sample can be 15mm*15mm*4mm.
[0025] In some possible implementations, the stainless steel sample material is martensitic stainless steel; the martensitic stainless steel includes medium carbon martensitic stainless steel, high carbon martensitic stainless steel or powdered steel.
[0026] Furthermore, the martensitic stainless steel samples may be subjected to different heat treatment processes. In this case, the morphology, size and distribution of carbides in the martensitic stainless steel may vary significantly, so that similarities and differences can be compared.
[0027] Furthermore, the method of grinding the cut surface includes at least one of rough grinding, fine grinding and polishing.
[0028] Furthermore, the medium carbon martensitic stainless steel includes 2Cr13, 3Cr13 or 4Cr13.
[0029] Furthermore, the high carbon martensitic stainless steel includes 5Cr15 or 9Cr18.
[0030] Furthermore, the powder steel includes S35VN and M390.
[0031] In some possible implementations, the pre-corrosion treatment lasts for 10 to 120 minutes. In this case, the sample can be fully passivated.
[0032] In some possible implementations, the electrochemical corrosion treatment step includes:
[0033] An electrochemical device with a three-electrode system is used to control the current and voltage of the electrochemical solution in which the pre-treated sample is immersed in stages.
[0034] Furthermore, the current is adjusted in a range of 0 mA to 200 mA, and the adjustment step is 5 mA to 50 mA. In this case, the chromium-poor region around the carbide in the sample will be activated, and the electrochemical corrosion solution will act on it.
[0035] Furthermore, the voltage adjustment range is ±20 V, and the adjustment step is 0.2 V to 2 V. In this case, the chromium-poor region around the carbide in the sample will be activated, and the electrochemical corrosion solution will act on it.
[0036] Furthermore, by adjusting the current and voltage in stages and gradient cycles, the chromium-poor area around the carbides and the nearby steel matrix can be completely corroded.
[0037] Furthermore, the electrochemical device is an electrochemical workstation, which can switch between a constant current source and a constant voltage source.
[0038] In some possible implementations, an electron microscope or an electron probe is used to obtain energy spectrum data of the sample to be tested.
[0039] In some possible implementations, obtaining the energy spectrum data of the sample to be tested includes the following steps:
[0040] First, obtain the composition data of the steel matrix: randomly collect more than 10 points on the surface of the steel sample, scan to obtain the energy spectrum data, and obtain the composition data, average the composition data, and then obtain the composition of the steel matrix. Based on the average result of the composition data, combined with the known composition of the steel, make corrections to play the role of a standard sample;
[0041] Similarly, three or more regions containing carbides are randomly selected to collect energy spectrum data to obtain the composition of the corresponding regions of the carbides.
[0042] In some possible implementations, energy spectrum processing software is used to reconstruct the energy spectrum data to obtain reconstructed data.
[0043] Furthermore, the reconstruction data screening basis is carbide M7C3 or M 23 Relative proportion of alloying elements in C6, threshold value 10%.
[0044] In some possible implementations, the data processing step includes: using Python software or Matlab to process the reconstructed data to obtain quantitative data of the carbide content in the sample to be tested.
[0045] The third object of the present invention is to provide an application of the quantitative statistical method for carbides in martensitic stainless steel provided by the present invention in the field of carbide detection in martensitic stainless steel, so as to provide a reference for judging the hardness and wear resistance of martensitic stainless steel.
[0046] In some possible implementations, the quantitative statistical method for carbides in martensitic stainless steel provided by the present invention is also applied to martensitic stainless steel containing other precipitated phases (such as nitrides, carbonitrides, etc.). BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1a This is a SEM morphology image of carbide in the sample to be tested in Example 1 of the present invention;
[0048] Figure 1b for Figure 1a A partial enlarged view of the SEM morphology image;
[0049] Figure 2 The XRD spectrum of the steel matrix of the sample to be tested in Example 1 of the present invention;
[0050] Figure 3 is the XRD spectrum of the carbide of the sample to be tested in Example 1 of the present invention;
[0051] Figure 4a The steel matrix distribution and statistical result diagram of the sample to be tested in Example 1 of the present invention;
[0052] Figure 4b The figure is a diagram showing the carbide distribution and statistical results of the sample to be tested in Example 1 of the present invention;
[0053] Figure 5 This is a SEM morphology image of the carbide of the sample to be tested in Example 2 of the present invention;
[0054] Figure 6 This is a SEM morphology image of the carbide of the sample to be tested in Example 3 of the present invention;
[0055] Figure 7 This is a SEM morphology image of the carbide of the sample to be tested in Comparative Example 1 of the present invention;
[0056] Figure 8 The steel matrix distribution and statistical result diagram of the sample to be tested in Comparative Example 1 of the present invention;
[0057] Fig. 9 The figure is a diagram showing the carbide distribution and statistical results of the sample to be tested in comparative example 1 of the present invention. DETAILED DESCRIPTION
[0058] In order to make the purpose, technical scheme and advantages of the implementation of the present invention clearer, the technical scheme in the embodiment of the present invention will be described in more detail below in conjunction with the drawings in the embodiment of the present invention. In the drawings, the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The described embodiments are part of the embodiments of the present invention, not all of the embodiments. The embodiments described below with reference to the drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limitations on the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. The embodiments of the present invention are described in detail below in conjunction with the drawings.
[0059] Example 1
[0060] Embodiment 1 provides an electrochemical etchant, including a pretreatment solution, an electrochemical solution and a post-treatment solution;
[0061] The pretreatment solution is 45 parts by volume of nitric acid and 15 parts by volume of anhydrous ethanol;
[0062] The electrochemical solution includes potassium thiocyanate, sulfuric acid and water; the weight volume ratio of the potassium thiocyanate, sulfuric acid and water is 2g:30ml:400ml.
[0063] The post-treatment liquid is 3 parts by volume of anhydrous ethanol.
[0064] This embodiment also proposes a quantitative statistical method for carbides in martensitic stainless steel, wherein the selected stainless steel material is 5Cr15MoV martensitic stainless steel after quenching at 1050°C; the method comprises the following steps:
[0065] (1) Obtain a stainless steel sample with a size of 15 mm*15 mm*4 mm.
[0066] (2) Grind the stainless steel sample until the surface is smooth and free of cutting marks.
[0067] (3) The polished sample is placed in anhydrous ethanol for ultrasonic cleaning to remove the surface oil film and obtain a clean stainless steel sample.
[0068] (4) The clean stainless steel sample was subjected to a pre-corrosion treatment for 30 minutes using the pre-treatment solution of this embodiment to obtain a pre-treated sample.
[0069] (5) Using a three-electrode electrochemical device to control the current and voltage of the electrochemical solution of this embodiment in which the pretreated sample is immersed in stages, an electrochemical corrosion sample is obtained. The current is adjusted in the range of 0 mA to 150 mA, with an adjustment step of 25 mA; the voltage is adjusted in the range of ±20 V, with an adjustment step of 2 V.
[0070] (6) The electrochemical corrosion sample is post-treated using the post-treatment solution of the embodiment of the present application to obtain a sample to be tested.
[0071] (7) Using an electron microscope to obtain a SEM morphology image of the carbide of the sample to be tested, such as Figure 1a , Figure 1b shown.
[0072] (8) Using an electron microscope to obtain energy spectrum data of the sample to be tested. Figure 2 The steel matrix XRD spectrum of the sample to be tested is shown in Figure 3 XRD patterns of the carbides are shown.
[0073] (8) reconstructing the energy spectrum data using energy spectrum processing software to obtain reconstructed data;
[0074] (9) The reconstructed data is processed using Matlab software to obtain the quantitative data of the carbide content in the sample to be tested, the steel matrix distribution and the statistical results are as follows: Figure 4a As shown in the figure, the distribution and statistical results of carbides are as follows Figure 4b The steel matrix and carbide content are shown in Table 1.
[0075] Example 2
[0076] Example 2 proposes an electrochemical etchant having the same components as the electrochemical etchant of Example 1.
[0077] This embodiment also provides a quantitative statistical method for carbides in martensitic stainless steel. The steps are basically the same as those in Embodiment 1, except that the stainless steel material is 3Cr13N nitrogen-containing martensitic stainless steel.
[0078] The SEM morphology of the carbide of the sample to be tested is obtained by electron microscopy, such as Figure 5 shown.
[0079] Example 3
[0080] Example 3 proposes an electrochemical corrosive agent, the components of which are basically the same as those of Example 1, except that the electrochemical solution is a hydrochloric acid aqueous solution with a mass fraction of 15%; and the post-treatment liquid is acetone with a volume fraction of 2 parts.
[0081] The SEM morphology of the carbide of the sample to be tested is obtained by electron microscopy, such as Figure 6 shown.
[0082] Comparative Example 1
[0083] Comparative Example 1 proposes a quantitative statistical method for carbides in martensitic stainless steel. The steps are basically the same as those in Example 1, except that: in step (5), only an electrochemical solution is used to pre-treat the sample, and no electrochemical device is added to apply voltage and current. An electron microscope is used to obtain a SEM morphology of the carbide of the sample to be tested, such as Figure 7 shown.
[0084] In order to verify the progress of the electrochemical etchant and the quantitative statistical method of carbides in martensitic stainless steel in the embodiment of the present invention, an electron microscope was used to obtain SEM images of the corrosion surfaces of the samples to be tested after corrosion in Examples 1 to 3 and Comparative Example 1, as shown in FIG. Figure 1a , Figure 1b , Figure 5 , Figure 6 , Figure 7 shown.
[0085] As an example, the energy spectrum of the sample to be tested in Example 1 is collected to obtain the following Figure 2 The XRD spectrum of the steel matrix of the sample to be tested is shown in Figure 3 The XRD spectrum of carbides, steel matrix distribution and statistical results are shown in Figure 4a As shown in the figure, the distribution and statistical results of carbides are as follows Figure 4b The energy spectrum of the sample to be tested in comparative example 1 is collected to obtain the steel matrix distribution and statistical results as shown in Figure 8 As shown in the figure, the distribution and statistical results of carbides are as follows Fig. 9 As shown. Figure 1a , Figure 1b , Figure 4a and Figure 4b The energy spectrum data of the corrosion surface of the sample to be tested are obtained. The steel matrix and carbide content obtained after processing in steps (8) and (9) are shown in Table 1 below. Figure 2 and Figure 3 The quantitative analysis results of the XRD patterns are shown in Table 2 below.
[0086] Table 1
[0087] Steel matrix content (%) Carbide content (%) Unrecognized (%) Example 1 80.2 17.7 2.1 Comparative Example 1 61.9 35.3 2.8
[0088] Table 2
[0089] Example 1 C(%) Cr(%) Fe(%) steel matrix 8.5 19.4 70.6 carbide 16.3 50.6 32.1
[0090] Depend on Figure 1a to Figure 9 , Table 1 and Table 2 above can at least draw the following conclusions:
[0091] ① The electrochemical corrosive agent of this embodiment is combined with the quantitative statistical method of carbides in martensitic stainless steel by electrochemical corrosion. The morphology of carbides in the sample to be tested obtained by corrosion is clearly visible. Then, the energy spectrum data is collected and processed, which can not only quantitatively obtain the carbide content in the sample to be tested, but also obtain the distribution of carbides.
[0092] ② By Figure 1a , Figure 5 and Figure 6 From the SEM image, it can be seen that the morphology and distribution of carbides in stainless steel after corrosion are easy to observe and distinguish, and the contrast difference between carbides and steel matrix is obvious. The positional relationship between carbides and matrix in martensitic stainless steel is fully displayed, with a strong three-dimensional sense.
[0093] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. An electrochemical corrosive agent, characterized in that: including a pre-treatment solution, an electrochemical solution and a post-treatment solution; The electrochemical solution comprises potassium thiocyanate, sulfuric acid and water; the weight volume ratio of the potassium thiocyanate, sulfuric acid and water is (1g-5g): (20ml-70ml): (300ml-500ml); Or the electrochemical solution includes a hydrochloric acid aqueous solution with a mass concentration of 10% to 24%.
2. The electrochemical corrosive agent according to claim 1, characterized in that: The pretreatment solution comprises 30 to 50 parts by volume of nitric acid and 10 to 20 parts by volume of anhydrous ethanol.
3. The electrochemical corrosive agent according to claim 1, characterized in that: The pretreatment solution includes concentrated nitric acid with a concentration of 8 mol / L or more or a mass fraction of 40% or more.
4. The electrochemical corrosive agent according to claim 1, characterized in that: The post-treatment liquid includes at least one of anhydrous ethanol, acetone and isopropanol.
5. The electrochemical corrosive agent according to any one of claims 1 to 4, characterized in that: The volume fraction of the post-treatment liquid is 2 to 10 parts.
6. A quantitative statistical method for carbides in martensitic stainless steel using the electrochemical corrosive agent according to any one of claims 1 to 5, characterized in that: The steps include: The clean stainless steel sample is pre-corroded by using a pre-treatment liquid to obtain a pre-treated sample; Performing electrochemical corrosion treatment on the pretreated sample using an electrochemical solution to obtain an electrochemically corroded sample; Post-treating the electrochemical corrosion sample with a post-treatment liquid to obtain a sample to be tested; The energy spectrum data of the corrosion surface of the sample to be tested is obtained, and the data is reconstructed and processed to obtain the quantitative data of the carbide content in the sample to be tested.
7. The quantitative statistical method for carbides in martensitic stainless steel according to claim 6, characterized in that: The time of the pre-corrosion treatment is 10 minutes to 120 minutes.
8. The quantitative statistical method for carbides in martensitic stainless steel according to claim 6, characterized in that: The electrochemical corrosion treatment step comprises: An electrochemical device with a three-electrode system is used to control the current and voltage of the electrochemical solution in which the pre-treated sample is immersed in stages.
9. The quantitative statistical method for carbides in martensitic stainless steel according to claim 8, characterized in that: The current adjustment range is 0mA to 200mA, and the adjustment step is 5mA to 50mA; And / or, the voltage adjustment range is ±20V, and the adjustment step is 0.2V to 2V; The current or voltage is applied in a staged and gradient cycle.
10. A quantitative statistical method for carbides in martensitic stainless steel according to any one of claims 6 to 9, and its application in the field of carbide detection in martensitic stainless steel.
